Digital workflow in the planning and execution of aesthetic oral rehabilitation: A literature review (Research, Society and Development, 2021)
Digital dentistry allows rehabilitation treatments to be carried out virtually. The dentist must choose the way of working, when inserting or not the digital workflow in the dental routine, seeking the most appropriate treatment for his patient. The aim of this study was to review the literature on the workdigital flow in the planning and execution of aesthetic oral rehabilitation. The search for the articles was carried out in the LILACS, Pubmed, Scopus and Google Scholar databases, using the keywords “Digital dentistry” “CAD/CAM” and “Esthetic”. English, Portuguese or Spanish studies, published between 01/2010 and 04/2021, were considered eligible. Advances in digital workflow enable treatment relatively quickly and more conveniently for the dentists, in addition to offering greater comfort to the patient. The technology offers numerous possibilities for prosthetic work, with properties similar to or superior to conventional procedures. Although it is expensive and requires training to use the system, the equipment has become less costly and more versatile, facilitating the work of the professional. Thus, with all in-office processing, from scanning to milling or 3D printing, it became possible to perform the entire restorative procedure in a single session. Thus, it is interesting to insert digital dentistry into the dental office, as it provides superior results to analogical dentistry.